2009
DOI: 10.1126/science.1174787
|View full text |Cite
|
Sign up to set email alerts
|

An Anomalous Basaltic Meteorite from the Innermost Main Belt

Abstract: Triangulated observations of fireballs allow us to determine orbits and fall positions for meteorites. The great majority of basaltic meteorites are derived from the asteroid 4 Vesta. We report on a recent fall that has orbital properties and an oxygen isotope composition that suggest a distinct parent body. Although its orbit was almost entirely contained within Earth's orbit, modeling indicates that it originated from the innermost main belt. Because the meteorite parent body would likely be classified as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 19 publications
4
110
1
Order By: Relevance
“…Based on the Bunburra Rockhole meteorite fall observations and sample recovery, Bland et al (2009) suggested that they may be surviving fragments of a differentiated parent body or bodies in the inner main belt different from those that form (4) Vesta. Based on triangulated observations of the fall, Bland et al (2009) determined the pre-entry orbit and estimated a probability of 98% that the observed meteoroid originated in the inner main belt and chances 72% of it originating from the ν 6 resonance (a main contributor to transporting asteroids from the Flora region Nesvornỳ et al 2002;Scholl & Froeschlé 1991). Furthermore, the meteorite oxygen isotopic composition in the recovered meteorites is significantly higher than that of howardite-eucrite-diogenite (HED) meteorites, which are commonly interpreted to be part of the Vesta family.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Bunburra Rockhole meteorite fall observations and sample recovery, Bland et al (2009) suggested that they may be surviving fragments of a differentiated parent body or bodies in the inner main belt different from those that form (4) Vesta. Based on triangulated observations of the fall, Bland et al (2009) determined the pre-entry orbit and estimated a probability of 98% that the observed meteoroid originated in the inner main belt and chances 72% of it originating from the ν 6 resonance (a main contributor to transporting asteroids from the Flora region Nesvornỳ et al 2002;Scholl & Froeschlé 1991). Furthermore, the meteorite oxygen isotopic composition in the recovered meteorites is significantly higher than that of howardite-eucrite-diogenite (HED) meteorites, which are commonly interpreted to be part of the Vesta family.…”
Section: Introductionmentioning
confidence: 99%
“…The Δ 17 O compositions of the three fractions are statistically indistinguishable, with an average value of -0.13 ± 0.04 ‰ (Bland et al, 2009). The oxygen isotopic composition of Bunburra is thus distinct from the HED fractionation line with Δ 17 O =0.24 ± 0.02 ‰.…”
Section: The Bunburra Rockhole Anomalous Basaltic Achondritementioning
confidence: 71%
“…1; Benedix et al, 2010;Bland et al, 2009) with similar modal composition. None of the three fractions of the Bunburra meteorite show significant evidence of intense shock pressures.…”
Section: The Bunburra Rockhole Anomalous Basaltic Achondritementioning
confidence: 95%
See 2 more Smart Citations